2017
DOI: 10.1002/chem.201700018
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of π‐Extended Viologens: Electron‐Deficient Polycyclic Aza‐aromatics

Abstract: A novel family of π-extended viologens has been synthesized by a concise 3-step route from simple and readily available chemicals. The π-enlargement gives the system new photophysical and electrochemical properties such as photoluminescence and changed redox potentials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Stable organic acceptors for which the first reduction potential is near 0 V, or even positive, are highly desirable for practical applications . Tuning the potential of viologen derivatives is commonly achieved by changing the N-substituent (either alkyl or aryl) or the counteranions. , Another more effective strategy that significantly facilitates the first reduction compared to that of methyl viologen (MV 2+ ) utilizes the introduction of main-group element or carbon bridges between the pyridyl moieties of the viologen framework. Few other reports describe the functionalization of the viologen’s carbon skeleton with electron-withdrawing groups as a method to alter its electronic properties …”
mentioning
confidence: 99%
“…Stable organic acceptors for which the first reduction potential is near 0 V, or even positive, are highly desirable for practical applications . Tuning the potential of viologen derivatives is commonly achieved by changing the N-substituent (either alkyl or aryl) or the counteranions. , Another more effective strategy that significantly facilitates the first reduction compared to that of methyl viologen (MV 2+ ) utilizes the introduction of main-group element or carbon bridges between the pyridyl moieties of the viologen framework. Few other reports describe the functionalization of the viologen’s carbon skeleton with electron-withdrawing groups as a method to alter its electronic properties …”
mentioning
confidence: 99%
“…9 and 10, and Supplementary Table 4). The two C-N bond lengths in the crystal structure of 7b are nearly identical (1.3492(18) and 1.3516(19) Å), and the average (1.350 Å) is comparable to the C-N bonds (1.34 Å) in N,N'-dibenzyl-dibenzodiazapyrene dication 14 21 . While from a structural perspective the C-N-C unit of 7b is similar to that in the pyridinium ring of 14, the neighboring NC-C bonds (1.420(2) and 1.421(2) Å) are slightly longer than the corresponding NC-C bonds in 14 (1.39 Å).…”
Section: Resultsmentioning
confidence: 90%
“…In 2017, Wei and Li et al reported a family of viologens ( N , N ′-disubstituted 4,4′-bipyridinium salts) in which the pyridyl rings are connected by two ortho -phenylene linkages ( Scheme 125 ). 254 First, phenylacetaldehyde and pyridine-4-carboxaldehyde underwent base-catalyzed condensation in a 2:1 stoichiometry to give a 1,5-dialdehyde intermediate, which was then condensed with hydroxylamine to generate the new pyridine ring in 125.1 . Owing to the electron-poor nature of 125.1 , subsequent cyclodehydrogenation did not take place when DDQ was used as the oxidant.…”
Section: Pyrenoidsmentioning
confidence: 99%
“… Reagents and conditions: (a) 254 (1) KOH, EtOH, 0 °C, rt, 26 h, (2) NH 2 OH·HCl, reflux, 2 h; (b) 5% HCl, hν (300 nm), air, rt, 24 h; (c) (1) MeI or RBr, DMF, 100 °C, 48 h, (2) KPF 4 , H 2 O, rt; (d) 255 I 2 , pyridine/1,4-dioxane, rt, 12 h; (e) TCNQ, MeCN, reflux, 20 h; (f) 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane, MeCN, reflux, overnight; (g) 256 (1) DMF, argon, 60 °C, 2 h, (2) toluene, Dean–Stark apparatus, 140 °C, 6 h; (h) (1) MeCN, O 2 , hν (300–400 nm), 14 h, (2) NH 4 PF 6 ; (i) 257 Fe(acac) 3 , AcOH, 90 °C, 12 h; (j) MeOTf, 1,2-DCE, 50 °C, 16 h; (k) Et 3 N, MeCN/DCM, argon, rt, 2 h. …”
Section: Pyrenoidsmentioning
confidence: 99%